Rich in Myth, Gold and Narrative: Aspects of the Central Otago Gold Rush, 1862-2012 - Carpenter, Lloyd (University of Canterbury. Humanities, 2013)
Abstract 150 years ago, the carefully-planned Presbyterian settlement of Dunedin was torn apart by the discovery that nearly every stream in Otago was laden with gold. The population exploded, adding the accents of Greece, Tipperary, Victoria, California, Guangdong and the King Country to the Scots burr which had been predominant. Almost immediately a myth of identity emerged, typified by goldfields balladeer Charles Thatcher’s ‘Old Identity and New Iniquity’ and boosted by the histrionics of a press enamoured of the romanticised machinations of the Otago goldfields ‘digger’. This popular mythology conflates the imagery of California, Victoria and early Gabriel’s Gully to perpetuate stories of desperate, gold-mad miners swarming across the province fighting, drinking and whoring away sparse winnings in a vast and lawless land, where bodies float down the Clutha, diggers battle corrupt police and vast fortunes are won and lost. This thesis seeks to construct a de-mythologised account of the rush for Central Otago gold, examining the engineering processes, social dynamics and communal relationships implicit in the development of claims, the construction of goldfields structures, the growth of towns and the emergence of financial networks. This explains and reveals the social, technological and economic developments of the gold rush that wrought a profound change on the Otago landscape and to New Zealand’s history. Focussing on the New Zealand Department of Conservation’s historic reserve at Bendigo as an exemplary site, this thesis focuses on the people of the goldfields who left traces of themselves in archives, letters, newspapers, court records and in the heritage landscape to explain their mining, commercial and family lives, and concludes by exploring the remnants of their existence in the relic-strewn ghost-town. By elucidating the depth and breadth of relationships, processes and lives of the residents, miners and merchants, I refute the pervasive myth of innocent simplicity around the era to replace it with a surprisingly complex reality. This complexity is revealed in the new conclusions I draw around the myriad processes behind identity formation, rush events, water race construction, quartz mine development and labour relations, merchant finances and heritage remnants.